Early Detection of Prostate Cancer: AUA/SUO Guideline Part I: Prostate Cancer Screening - Wei, John T; Barocas, Daniel; Carlsson, Sigrid; Coakley, Fergus; Eggener, Scott; Etzioni, Ruth; Fine, Samson W; Han, Misop; Kim, Sennett K; Kirkby, Erin; Konety, Badrinath R; Miner, Martin; et al. (The Journal of urology, 2023)
The summary presented herein covers recommendations on the early detection of prostate cancer and provides a framework to facilitate clinical decision-making in the implementation of prostate cancer screening, biopsy, and follow-up. This is Part I of a two-part series that focuses on prostate cancer screening. Please refer to Part II for discussion of initial and repeat biopsies as well as biopsy technique. The systematic review utilized to inform this guideline was conducted by an independent methodological consultant. The systematic review was based on searches in Ovid MEDLINE and Embase and Cochrane Database of Systematic Reviews (January 1, 2000-November 21, 2022). Searches were supplemented by reviewing reference lists of relevant articles. The Early Detection of Prostate Cancer Panel developed evidence- and consensus-based guideline statements to provide guidance in prostate cancer screening, initial and repeat biopsy, and biopsy technique. Prostate-specific antigen (PSA)-based prostate cancer screening in combination with shared decision-making (SDM) is recommended. Current data regarding risk from population-based cohorts provide a basis for longer screening intervals and tailored screening, and the use of available online risk calculators is encouraged.